Firecracker!

Algebra Level 4

Let p ( x ) = x 2 5 x + a p(x) = x^2-5x +a and q ( x ) = x 2 3 x + b q(x) = x^2-3x+ b where a a and b b are positive integers. Suppose gcd ( p ( x ) , q ( x ) ) = x 1 \gcd(p(x), q(x)) = x- 1 and denote k ( x ) = lcm ( p ( x ) , q ( x ) ) k(x) = \text{lcm}(p(x),q(x)) . Find the sum of all distinct roots of ( x 1 ) + k ( x ) (x-1) + k(x) .


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Akshat Sharda
Nov 2, 2015

As the hcf ( p ( x ) , q ( x ) ) = x 1 p ( x ) = x 2 5 x + 4 and q ( x ) = x 2 3 x + 2 x 2 5 x + 4 = ( x 1 ) ( x 4 ) and x 2 3 x + 2 = ( x 1 ) ( x 2 ) k ( x ) = lcm ( p ( x ) , q ( x ) ) = ( x 1 ) ( x 2 ) ( x 4 ) ( x 1 ) + k ( x ) = ( x 1 ) + ( x 1 ) ( x 2 ) ( x 4 ) = ( x 1 ) ( x 2 6 x + 9 ) = ( x 1 ) ( x 3 ) 2 Sum of all distinct roots = 1 + 3 = 4 \text{As the hcf}(p(x),q(x))=x-1\Rightarrow p(x)=x^{2}-5x+4 \text{ and }q(x)=x^{2}-3x+2 \\ x^{2}-5x+4=(x-1)(x-4) \text{ and }x^{2}-3x+2=(x-1)(x-2) \\ k(x)=\text{lcm}(p(x),q(x))=(x-1)(x-2)(x-4) \\ (x-1)+k(x)=(x-1)+(x-1)(x-2)(x-4)=(x-1)(x^{2}-6x-+9)=(x-1)(x-3)^{2} \\ \text{Sum of all distinct roots}=1+3=\boxed{4}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...